Innovative Development of Belarus - Hrechyshkina, Olena; Samakhavets, Maryia (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
This paper is intended to investigate the current status and prospects of the innovative development of Belarus. The estimation of the innovative environment is based on Belarusian official statistical indicators and State program documents. Scientific research methods, the analytical method, comparative analysis are used in the study and treatment of the material. The analysis reveals a relatively low innovative activity of organisations in Belarus. The results indicate the need to further improve the environment for the development of innovations in Belarus.